The application of the Yo-Yo intermittent endurance level 2 test to elite female soccer populations - Bradley, P. S.; Bendiksen, M.; Dellal, A.; Mohr, M.; Wilkie, A.; Datson, N.; Orntoft, C.; Zebis, M.; Gomez-Diaz, A.; Bangsbo, J.; Krustrup, P. (Scandinavian Journal of Medicine & Science in Sports, 2014)
The aim of this study was to evaluate the application of the Yo-Yo intermittent endurance test level 2 (Yo-Yo IE2) to elite female soccer populations. Elite senior (n = 92), youth (n = 42), domestic (n = 46) and sub-elite female soccer players (n = 19) carried out the Yo-Yo IE2 test on numerous occasions across the season. Test-retest coefficient of variation (CV) in Yo-Yo IE2 test performance in domestic female players was 4.5%. Elite senior female players' Yo-Yo IE2 test performances were better (P < 0.01) than elite youth, domestic and sub-elite players (mean ± standard deviation; 1774 ± 532 vs 1490 ± 447, 1261 ± 449, and 994 ± 373 m). For elite senior female players, wide midfielders (2057 ± 550 m) had a higher Yo-Yo IE2 test performance (P < 0.05) than central defenders (1588 ± 534 m) and attackers (1516 ± 401 m), but not central midfielders (1764 ± 473 m) or full-backs (1964 ± 522 m). Large correlations were observed between Yo-Yo IE2 test performance and the total and high-intensity distance covered (r = 0.55; P < 0.05) during elite senior soccer matches (r = 0.70; P < 0.01). A large correlation was also obtained between Yo-Yo IE2 test performance and inline image (r = 0.68; P < 0.01). Performances in the Yo-Yo IE2 test were greater (P < 0.05) in the middle and the end of the season compared with the preparation period for elite youth female players (1767 ± 539 and 1742 ± 503 vs 1564 ± 504 m) and in elite senior female players, Yo-Yo IE2 test performance increased by 14% (P < 0.01) after completing 4 weeks of intense training prior to the FIFA Women's World Cup Finals (2049 ± 283 vs 1803 ± 342 m). The data demonstrate that the Yo-Yo IE2 test is reproducible and is an indicator of the match-specific physical capacity of female soccer players. Furthermore, the Yo-Yo IE2 test illustrates sensitivity by differentiating intermittent exercise performance of female players in various competitive levels, stages of the season and playing positions.